2018
DOI: 10.5021/ad.2018.30.2.150
|View full text |Cite
|
Sign up to set email alerts
|

Can the Cytokine Analysis of the Scales on Alopecic Patch Predict the Response to Diphenylcyclopropenone Treatment in Alopecia Areata Patients?

Abstract: BackgroundContact immune modulating therapy with diphenylcyclopropenone (DPCP) is a topical treatment option for extensive alopecia areata (AA). Because the response to DPCP treatment varies according to the patient, and it takes several months to evaluate the clinical effectiveness of the treatment, it is necessary to identify the factors that can predict the prognosis of the disease while treating with topical DPCP.ObjectiveIn this study, cytokine levels in the scales of alopecic patches were investigated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“… 34 However, additional studies would be required to confirm the role of regulatory cytokines in AA, since Lee et al had reported no significant difference in the IL-10 levels of scale samples from patients (responders vs nonresponders) after receiving topical immunotherapy. 55 Gong et al demonstrated that patients with pretreatment showed elevated Th1-cytokines, using IL-12 as the marker, and could be good candidates for DPCP therapy. Patients with elevated Th2-cytokines, such as IL-4, can counteract the immune response elicited by topical immunotherapy, leading to poor treatment response.…”
Section: Topical Immunotherapy and Alopecia Areatamentioning
confidence: 99%
“… 34 However, additional studies would be required to confirm the role of regulatory cytokines in AA, since Lee et al had reported no significant difference in the IL-10 levels of scale samples from patients (responders vs nonresponders) after receiving topical immunotherapy. 55 Gong et al demonstrated that patients with pretreatment showed elevated Th1-cytokines, using IL-12 as the marker, and could be good candidates for DPCP therapy. Patients with elevated Th2-cytokines, such as IL-4, can counteract the immune response elicited by topical immunotherapy, leading to poor treatment response.…”
Section: Topical Immunotherapy and Alopecia Areatamentioning
confidence: 99%
“…Yonei et al (2007) detected that TCA induced production of growth factors and cytokines, including platelet-derived growth factor, vascular endothelial growth factor, keratinocyte-derived growth factor, and interleukin-10 (IL-10) 19 . Reviewing the literature, it was found that IL-10 has an anti-inflammatory action 20 and that it was elevated in scalp following diphenylcyclopropenone (DPCP) treatment. 21 Also, vascular endothelial growth factor (VEGF) stimulates angiogenesis providing nutritional needs of follicles.…”
Section: Significant Reduction In Trichoscopic Parameters Indicatingmentioning
confidence: 99%
“…Moreover, even patients with good responses to JAK inhibitors require long-term administrations of the drug because AA easily relapses 2.7 months after the cessation of the drug [ 7 ]. As there are no established biomarkers of AA, which would reflect disease activities and therapeutic responses, many researchers have made substantial efforts to reveal biomarkers of AA, which patients would be indicated for JAK inhibitors, or other treatments such as DPCP [ 8 , 9 ]. There is some evidence that elevated serum levels of IL-4 and IL-12 before treatment suggest unfavorable response to DPCP in AA patients [ 8 ].…”
Section: Introductionmentioning
confidence: 99%